An analysis of abstracts in medical and economics journals: Microstructure and practical applications - Mureşan, Oana; Kic-Drgas, Joanna (Glottodidactica, 2019)
Writing abstracts, both in a professional and academic environment, is a crucial skill, reflecting the ability to think synthetically and express thoughts in a concise way. Due to the rising popularity of indexing scientific papers in different databases, abstracts can determine the readability of a paper and its future quotation rate. This paper presents the results of an analysis of the microstructure of 40 abstracts from prestigious impact factor medical and economics journals, offering guidelines for designing abstract writing exercises in foreign language courses for specific purposes